NEW MEANING OF I'JÂZ AL-QUR`ÂN IN M. QURAISH SHIHAB'S THINKING - Musyafa, Mochamad Choirul; Abidin, Ahmad Zainal (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2021)
Abstract The meaning of I’jaz underwent development in the hand of Quran believers. Quraish Shihab, one of Indonesia mufassir said that the Holy Quran and its miracles do not know the limit of time and space. In ‘Ulûm al-Qur`ân, the speciality which is owned by the Holy Quran is its miracle’s aspects. Those aspects include the spects of its literary, law and creed, science and unseen signals. According to Quraish Shihab, the speciality of the Holy Quran is divided into two; miracles and privileges. For him, the miracle’s aspects of the Holy Quran are literary aspects, scientific and unseen signals. While the privilege of the Holy Koran are another things which are not included in the Holy Koran’s miracles. The things under consideration to say about the miracle of the Holy Quran is that the Prophet Muhammad is an ummî, social circumstances of the Arab community when The Holy Koran was revealed and the type of the Holy Quran’s gradual revelation in some years. Keywords: I’jaz, Miracle, Privilege, Ummi Abstrak Makna I'jaz mengalami perkembangan di tangan orang-orang yang mengimani Al-Quran. Quraish Shihab sebagai salah satu mufassir Indonesia mengatakan bahwa Alquran dan mukjizatnya tidak menegenal batas waktu dan ruang. Dalam ‘Ulûm Al-Quran, kekhasan yang dimiliki oleh Al-Quran adalah aspek i’jaz-nya. Aspek itu meliputi sastra, hukum dan kepercayaan, sains dan isyarat gaib. Menurut Quraish Shihab, kekhasan atau spesialisasi Al-Quran dibagi menjadi dua; keajaiban dan hak istimewa. Baginya, aspek mukjizat Al-Quran adalah aspek sastra, ilmiah dan berita gaib. Sementara keistimewaan Alquran adalah aspek lain yang tidak termasuk dalam mukjizat Alquran. Hal-hal yang mesti dipertimbangkan untuk mengatakan tentang realitas mukjizat Al-Quran adalah bahwa Nabi Muhammad SAW tidak bisa baca tulis (ummî), keadaan sosial jahiliyyah masyarakat Arab ketika Al-Quran diturunkan dan pola pewahyuan Al-Quran bertahap dalam beberapa tahun. Kata kunci: I'jaz, Keajaiban, Keistimewaan, Ummi